Numerical simulation of the high-temperature oxidation of a nanosize aluminum particle; Journal of Engineering Physics and Thermophysics; Vol. 94, iss. 1 - Kraynov A. Yu. Aleksey Yurjevich; Poryazov V. A. Vasily Andreevich; Moiseeva K. M. Kseniya Mikhaylovna; Kraynov (Krainov) D. A. Dmitry Alekseevich (2021, 2021)
Title screen